THE EFFECT OF CUSTOMER INTIMACY, CUSTOMERS EXPERIENCE, CUSTOMER SATISFACTION AND CUSTOMER BONDING ON CUSTOMER LOYALTY AT BANK BRI SYARIAH KCP PANDA'AN PASURUAN - Miftahul Huda (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2020)
Indonesia's economic development, which is increasingly advanced, especially in the field of Islamic banking. The development of Islamic banking in Indonesia gave birth to so many investors and customers with various fundraising. High public interest in Islamic banks in saving and financing makes the banking sector more prospective. In this case, making competition in Islamic banking more competitive, especially for sharia-based banks with the same target market segment, Islamic banks have increased significantly from year to year. From this opportunity, many Islamic banks in Indonesia competed in order to meet customer needs. In this case, Islamic banks have an important role, namely to always meet customers' needs, provide products or services that are ethical following sharia principles, and provide the most comfortable access through various means anytime, anywhere. This research is an explanatory research that aims to determine the effect of Customer Intimacy, Customer Experience, Customer Bonding, Customer Satisfaction on customer loyalty. In this case, researchers take samples at Bank. In Syariah KCP Pandaan. The sample used was 92 respondents, namely customers at BRI Syariah KCP Pandaan, the sampling technique used was a pursosive r; the sampling method. This type of purposive research with a quantitative approach. The data used are primary data. Primary data were obtained based on results' answers to questionnaires distributed to customers at BRI Syariah KCP Pandaan Bank. Analysis of the data used is multiple linear regression analysis.